Adaptation of the Fears of Compassion Scale into Turkish: a reliability and validity study - Necef, Isil; Deniz, Mehmet Engin (TERMEDIA PUBLISHING HOUSE LTD, 2023)
BACKGROUND The concept of fear of compassion draws the interest of researchers in both clinical and scientific fields. The Fears of Compassion Scale (FCS) was developed in order to ex-amine the fear of compassion for others, compassion from others and compassion for one's self. This study aims to adapt the FCS into the Turkish language. The Satisfaction with Life Scale and the Self-Compassion Scale were used to assess the criterion-related validity of the FCS. PARTICIPANTS AND PROCEDURE In order to determine the construct validity of the scale, validity and reliability studies and factor analysis were carried out on 681 participants (Mage = 32.00, SD = 10.15; 64% female and 36% male).RESULTS The results of the confirmatory factor analysis yielded the expected 3-factor solution (the fear of compassion for others, the fear of compassion from others and the fear of self-compassion), which consists of 35 items. The internal consistency validity coefficient of the whole scale was .92. Moreover, there were significant negative relationships be-tween the Fears of Compassion Scale, the Satisfaction with Life Scale and Self-Compassion Scale, which are similar to those of the original scale.CONCLUSIONS These significant findings reveal the Turkish adaptation of the FCS to be a valid and reliable measurement tool.
Keywords: compassion; fear of compassion; validity; reliability; scale adaptation; ATTACHMENT SECURITY; SELF-COMPASSION; ALEXITHYMIA; EXPLORATION; DEPRESSION; HAPPINESS; THERAPY; Psychology